Seroprevalence of the Strongyloides stercoralis infection in humans from Yungas Rainforest and Gran Chaco Region from Argentina and Bolivia - Cimino, Rubén Oscar (2020)
The threadworm, Strongyloides stercoralis, is endemic in tropical and subtropical areas. Data on the prevalence and distribution of infection with this parasite species is scarce in many critical regions. We conducted a seroprevalence study of S. stercoralis infection in 13 locations in the Gran Chaco and Yungas regions of Argentina and Bolivia during the period 2010–2016. A total of 2803 human serum samples were analyzed by ELISA-NIE which has a sensitivity of 75% and specificity of 95%. Results showed that 551 (19.6%) of those samples were positive. The adjusted prevalence was 20.9%, (95% confidence interval (CI) 19.4–22.4%). The distribution of cases was similar between females and males with an increase of prevalence with age. The prevalence in the different locations ranged from 7.75% in Pampa del Indio to 44.55% in Santa Victoria Este in the triple border between Argentina, Bolivia, and Paraguay in the Chaco region. Our results show that S. stercoralis is highly prevalent in the Chaco and Yungas regions, which should prompt prospective surveys to confirm our findings and the design and deployment of control measures.